Xác định hệ số sử dụng thời gian cho nghiên cứu và phát triển của giảng viên trong cơ sở giáo dục đại học, trường cao đẳng để tính toán chỉ tiêu cán bộ nghiên cứu theo tương đương toàn thời gian (FTE) - Tào, Hương Lan (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
This article presents the results of the statistical survey to determine the time-use coefficient for research and development (R&D) of lecturers in universities and colleges aiming to estimate the number of researchers by FTE (full time equivalent). In order to determine time-use coefficient for R&D, we have applied a statistical method to consider the average of the time ratio spent on R&D of the entire sample under two options: multistage sampling with subdivision and adding a table in R&D questionnaire. The result shows that the time-use coefficient with the option 1 and the option 2 are 31.09% (or 0.31) and 29.41% (or 0.29), respectively.